Halal Tourism in the Context of Tourism Sector in Tunisia: Controversies, Challenges, and Opportunities (Mazahib, 2020)
This paper examines the development of the tourism industry in Tunisia from its independence in 1956 to contemporary Tunisia with a special focus on the development of halal tourism. In assessing the tourism sector in Tunisia, a typology is used. This typology makes it clear that Tunisia is a prominent tourist destination in several types of tourism, including beach tourism, while in other types it remains underdeveloped. Regarding the emerging form of halal tourism, Tunisia is lagging behind in its development. This may come as a surprise given the fact that Tunisia is a popular tourist destination and a Muslim majority country. Although there are different reasons for this, I would argue that many things can be explained by looking at the political context in Tunisia. The reluctance of government actors hinders the profound development of halal tourism. The policies that have been put forward in the past by Bourguiba and Ben Ali have had an undeniable impact on the general opinion of contemporary Tunisian society on this matter. Even though Tunisia is faced with challenges, Tunisia can still be a suitable country for halal tourism while maintaining other forms of tourism.Keywords: Tunisia, halal tourism, religious tourism, opportunities and challenges.